The Permissibility, Potentials and Management of Waqf al-Manafi’ (Usufruct Endowment): Pondok Modern Tazakka’s Experience - Subhi Mahmassani; Hakim As Shidqi; Ahmad Afandi; Alip Sodiq; Ferry Hidayat (Proceeding of International Conference on Islamic Boarding School, 2025)
This paper explores the permissibility, potentials, and effective management of waqf al-manafi’ (usufruct endowment) within the framework of Islamic jurisprudence, with a particular focus on the Malikite school. It examines how this form of endowment—when entrusted to a competent and knowledgeable nazhir (waqf manager)—can significantly enhance the sustainability of quality education in pesantrens and contribute to the economic welfare of the Muslim community. By analyzing the case of Pondok Modern Tazakka, the study highlights a successful model of waqf al-manafi’ implementation. The research demonstrates how the systematic management of endowments has enabled Pondok Modern Tazakka to maximize their impact, ensuring financial stability and fostering the institution’s educational mission. This paper provides valuable insights into the role of waqf al-manafi’ in empowering Islamic education and offers a practical framework for optimizing its benefits within contemporary pesantren settings